From Social Media to Showroom: How Hyundai Leverages Influencer Marketing to Shape Consumer Purchase Decisions and Brand Image - Sanawiri, Brillyanes; Siregar, Marsa Malikiya; Irawan, Ari; Agusti, Rosalita Rachma; Sumantri, Bambang Agus (PINISI Discretion Review, 2025)
This study aims to analyze the influence of influencer marketing and social media marketing on brand image and purchase decision, with brand image as a mediating variable. The theories used in this study include source credibility, self-congruity, and stimulus-organism-response, which explain how these two digital marketing variables affect consumer perceptions and their decision-making. The research uses a structured survey approach in the automotive sector, with Partial Least Squares-Structural Equation Modeling (PLS-SEM) as the analysis technique. The results show that influencer marketing and social media marketing have a significant positive impact on brand image and purchase decision. Brand image is proven to mediate the relationship between influencer marketing, social media marketing, and purchase decision, confirming the important role of brand image in the consumer decision-making process. These findings support the relevance of the theories used in digital marketing. Practically, the results of this study have implications for companies to prioritize the credibility and congruence between influencers and brands in their social media marketing strategies. The research also highlights the importance of transparency in influencer collaborations to build consumer trust. Limitations of the study include the use of data collected at a single point in time, which limits the ability to draw causal conclusions, as well as the automotive industry context, which may affect generalizability. Future research is recommended to use longitudinal or experimental designs to explore the negative effects of influencer marketing and social media marketing.